UV-curable coating process on CMYK-printed duplex paperboard, part I: mechanical and optical properties - Soltani, Mojtaba; Veisi, Ramin; Rohani, Ali Asghar; Naji, Hamid Reza; Bakar, Edi Suhaimi (North Carolina State University, 2014)
An ultraviolet (UV)-curable coating is one of the best finishing methods in the paper and packaging industries for protecting ink layers from physical and mechanical defects. The purpose of this study was to investigate the mechanical and optical properties of CMYK printed paperboard after coating it with the UV-curable varnish. Commercial duplex paperboard (glazed grayback paperboard, 230 g/m2) was printed with a CMYK offset printing process. After conditioning the printed samples, they were coated with a commercial UV-curable varnish (consisting of a liquor-to-solvent ratio of 50:50) using an industrial screen-coating machine. The samples were then dried using a UV lamp in an industrial UV drying machine. The discoloration of the CMYK ink layers was measured spectrophotometrically using CIELab parameters (L*, a*, b*, and ΔE) before and after the coating process. The whiteness, brightness, and fold and tear resistance of the ink films were also measured. Color change (ΔE) was recorded for all tested samples, and the least amount of discoloration was observed in CYAN ink. The highest variances of the relative optical parameters were found in the MAGENTA, YELLOW, and BLACK ink ﬁlms, which resulted in yellowing of the coated paperboard. It can therefore be concluded that the coating process significantly decreased the fold and tear resistance of the samples.